Adapted mathematical games: A comparative study of Spain and the United States (Revista Universitaria del Caribe, 2025)
This comparative analysis explores the use of adapted mathematical games in Spanish and US inclusive classrooms for students with learning disabilities, neurodiversity, and other special needs. The analysis, based on information from 24 schools (12 per country), uses surveys, interviews, classroom observations, and policy analysis. Findings reveal that American teachers routinely adapt games according to Universal Design for Learning (UDL) principles, individual education plans (IEPs), and differentiated instruction. The adaptations are more formalized, supported by training, and embedded in curriculum objectives. Spanish teachers, although affirmative about game playing, use games less frequently and undertake more improvisation since they have less access to formal training and more formalized curricula. Students in both environments enjoy games, but only American students show sustained gains in school performance from modified gameplay. Spanish classrooms prefer to employ games as an incentive rather than as a pedagogy, with fewer accommodations for differences in needs. Cultural attitudes toward differentiation and disability also shape implementation: American schools prefer individualism and autonomy, whereas Spanish schools lean toward group cohesion and standardization. The study discovers that modified games hold immense promise for inclusion if they are designed to their specifications and adequately supported. It recommends additional professional development, curriculum flexibility, and culturally responsive practices in modification. Highlighting strengths and limitations at the national level provides insight into future classroom practice, training, and policy for inclusive mathematics education.